Faktor Risiko Terjadinya Infeksi Daerah Operasi pada Pasien Bedah Orthopedi di RSUP Fatmawati Periode Juli-Oktober 2018 - Asrawal Asrawal; Ros Summary; Delina Hasan; Debby Daniel (Jurnal Sains Farmasi & Klinis, 2019)
Background: Surgery is one of the basic components of very important health care system. Therefore, the risk of any infectionin the surgical process must be known because microbes maycome in or accidentally come into the limbs that are in surgery. Microbes can cause nosocomial infections or Health Care Associated Infections (HAIs).WHO survey shows 5% -34% of HAIs are SSI while the highest prevalence of HAIs occurs intensively in care units, acute surgery and orthopedic rooms. Thisresearch aims to determine SSI and risk factors for SSI in orthopedic surgery patients at Fatmawati Hospital in July-October 2018. Method: This research was observational using cross sectional design,in whichthe data collection wasperformed prospectively. Data analysis was performed by univariate, bivariate, and multivariate analytic using total sampling from patients who performed orthopedic surgery at Fatmawati Hospital in both elective and cito surgery on July-October 2018 and SSI data collection was performed after surgery, namely in orthopedic poly outpatient care and inpatient care. Result: Data obtained in this research showed SSI level is 3.9 % of Orthopedic Surgery (3.9% cases of a total  770) in the research period. The results of the chi-square analysis showed that the diabetes mellitus, ASA score and type of surgery had a significant relationship with the incidence of SSI with significance value diabetes mellitus that is 0.024; ASA score that is 0.035 and type of surgery that is 0.001 where p <0.05, while the use of prophylactic antibiotics and other risk factors did not have a significant relationship,in which because p>0.05. Analysis with logistic regression showed that the type of operation had a significant influence with the incidence of SSI which was 0.004 (p <0.05). Conclusion: From this research, it can be inferred that this type of surgery can increase the occurrence of SSI. Therefore, it is necessary to evaluate to reduce the rate of surgical site infections.